The Deductions of al-Imām al-Jushamī in Surat al-Fātiḥah Through His Exegesis in al-Tahdhīb fī al-Tafsīr: An Analytical Study - Souilah Akram Abdel Bari; Samir El Hosry; Abdelali Bey Zekkoub (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
This research aims to investigate the deductions found in Surat Al- Fātiḥah in the interpretation of al-Imām al-Jushamī , , and critically examine them . The research problem arises from the fact that these deductions have not been previously compiled or studied comprehensively, with some being acknowledged by scholars . While his deductions have strengths, they also face criticism, highlighting the significance of this research in elucidating and critiquing al-Imām al-Jushamī’s deductions in Surat al-Fātiḥah.The researcher adopted an inductive and analytical approach. The study yielded several findings, notably that deduction is a science that tolerates right and wrong, and that deviation in interpretation and doctrine is one of the main reasons for error in deduction. Likewise, Al-Hakim Al-Jashmi paid attention to the aspect of deduction in his interpretation, and he  summarized the opinions of the predecessors and explained them as best as possible.